Effect of Nisin-based pretreatment solution on dentin bond strength, antibacterial property, and MMP activity of the adhesive interface - Campos, Raquel Pinto [UNESP]; Mailart, Mariane Cintra [UNESP]; Matuda, Amanda Guedes Nogueira [UNESP]; Yui, Karen Cristina Kazue [UNESP]; Chagas, Gabriela da Silva [UNESP]; Rocha, Marcella Batista [UNESP]; Tay, Franklin R.; Pucci, Cesar Rogerio [UNESP] (Elsevier, 2024)
Objective: To evaluate the effect of a Nisin-based dentin pretreatment solution on microtensile bond strength, antibacterial activity, and matrix metalloproteinase (MMP) activity of the adhesive interface. Materials and methods: 100 human molars were sectioned to expose dentin. The teeth were assigned to five groups (n = 20), according to the dentin pretreatment: 0.5%, 1.0%, or 1.5% Nisin; 0.12% chlorhexidine (positive control), and no solution (negative control), and divided into 2 subgroups: no aging, and thermomechanical aging. Specimens were etched with 37% H3PO4 for 15 s and submitted to the dentin pretreatment. Then, they were bonded with an adhesive (Adper Single Bond 2) and a resin composite for microtensile bond strength (μTBS) evaluation. Antibacterial activity against Streptococcus mutans was qualitatively examined using an agar diffusion test. Anti-MMP activity within hybrid layers was examined using in-situ zymography. Data were analyzed with two-factor ANOVA and post-hoc Tukey's test (α = 0.050). Results: For μTBS, significant differences were identified for the factors “solutions” (p = 0.002), “aging” (p = 0.017), and interaction of the two factors (p = 0.002). In the absence of aging, higher μTBS was observed for the group 0.5% Nisin. In the presence of aging, all groups showed similar μTBS values. All Nisin concentrations were effective in inhibiting the growth of S. mutans. Endogenous MMP activity was more significantly inhibited using 0.5% and 1.0% Nisin (p < 0.050). Conclusion: 0.5% and 1.0% Nisin solutions do not adversely affect resin-dentin bond strength and exhibit a potential bactericidal effect against S. mutans. Both concentrations effectively reduce endogenous gelatinolytic activity within the hybrid layer. Clinical relevance: The use of 0.5% and 1.0% Nisin solutions for dentin pretreatment potentially contributes to preserving the adhesive interface, increasing the longevity of composite restorations.
Keywords: Antibacterial activity; Bond strength; Dentin; MMP inhibition; Nisin